2018
DOI: 10.1590/1678-7757-2017-0414
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between phonological working memory, metacognitive skills and reading comprehension in children with learning disabilities

Abstract: Reading requires the activation of several cognitive processes, some of which are basic, e.g. recognizing letters and words, whereas others are complex, such as working memory and ability to think about one's own learning strategies. One condition for fulfilling a complex cognitive task, such as understanding a text, is the ability to maintain and process information, which depends on working memory.ObjectiveTo analyze the ability of using metacognitive strategies for reading, the phonological working memory o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 24 publications
(32 reference statements)
1
15
1
2
Order By: Relevance
“…In this study, there was not observed an initial deficit in PL in children with reading comprehension difficulties, a datum different from other studies comparing WM between children with/without difficulties in academic domains. The difference in results between this study and others found in literature may be related to the diversity of the sample regarding age (evaluation of children in the beginning of their literacy process) 19 , level of seriousness of learning disorders 16,17 , complexity of the tests used for WM evaluation (e.g., backward digit repetition) 6,23,29 , or due to statistical analysis (correlation tests) 7,36 .…”
Section: Resultscontrasting
confidence: 91%
See 4 more Smart Citations
“…In this study, there was not observed an initial deficit in PL in children with reading comprehension difficulties, a datum different from other studies comparing WM between children with/without difficulties in academic domains. The difference in results between this study and others found in literature may be related to the diversity of the sample regarding age (evaluation of children in the beginning of their literacy process) 19 , level of seriousness of learning disorders 16,17 , complexity of the tests used for WM evaluation (e.g., backward digit repetition) 6,23,29 , or due to statistical analysis (correlation tests) 7,36 .…”
Section: Resultscontrasting
confidence: 91%
“…Significant improvement in academic aspects of reading/writing and reading comprehension in G1 may be explained by the existing relation between working memory and learning aspects. Literature reports that working memory is essential to reading development, and that children with difficulties at school have deficits in this ability [5][6][7][8][15][16][17][18][19] .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations